The translator as an expert witness in court - Rocco Loiacono (Translation and Interpreting : the International Journal of Translation and Interpreting Research, 2022)
In the matter of R v Yang the Supreme Court of Western Australia considered the role of a translator as an expert witness. In this particular case, the Court had to consider the accuracy and relevance of a translation provided in a criminal trial. The Court analysed in detail the role of the translator in the criminal legal process and how that related to his ethical obligations of accuracy and impartiality. In doing so, the Court also had to apply the law related to expert witnesses generally, and when that evidence could be excluded. This article analyses the role of the translator as an expert witness in legal proceedings and comments on the necessity for all parties, but especially translators, to have a proper understanding of their role and ethical obligations in this regard, where a premium on accuracy and impartiality is arguably at its highest.